2021
DOI: 10.1002/jaba.883
|View full text |Cite
|
Sign up to set email alerts
|

Extending functional communication training to multiple language contexts in bilingual learners with challenging behavior

Abstract: Little research has highlighted how evidence‐based practices (e.g., functional communication training [FCT]) might be adapted for bilingual learners with disabilities. In the current study, we served 2 children with autism spectrum disorder (ASD) and challenging behavior whose parents primarily spoke Spanish at home, and whose teachers primarily spoke English at school. Following traditional FCT (i.e., 1 language only), we systematically replicated the findings of Neely, Graber et al. (2020) by demonstrating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…For example, an individual with challenging behavior that is maintained by access to both attention and tangibles may continue to engage in challenging behavior (i.e., low treatment efficacy) if they are taught a communicative response for attention in the absence of tangible items. Another basis for selecting this variable was the potential influence of previously taught mands on treatment efficacy for newly taught mands (e.g., Banerjee et al, 2022; Bloom & Lambert, 2015; Lambert, Bloom, et al, 2017; Lambert et al, 2015, 2020; although see Fuhrman et al, 2021), which was specific to individuals with multiply controlled challenging behavior in our sample. That is, acquisition of multiple communication responses, separately across reinforcer classes, may result in higher efficacy in subsequent training applications via a process of generalization; alternatively, acquisition of multiple communication responses across reinforcer classes may result in relatively more errors (e.g., emission of previously taught responses that contact extinction) that may temporarily increase rates of challenging behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an individual with challenging behavior that is maintained by access to both attention and tangibles may continue to engage in challenging behavior (i.e., low treatment efficacy) if they are taught a communicative response for attention in the absence of tangible items. Another basis for selecting this variable was the potential influence of previously taught mands on treatment efficacy for newly taught mands (e.g., Banerjee et al, 2022; Bloom & Lambert, 2015; Lambert, Bloom, et al, 2017; Lambert et al, 2015, 2020; although see Fuhrman et al, 2021), which was specific to individuals with multiply controlled challenging behavior in our sample. That is, acquisition of multiple communication responses, separately across reinforcer classes, may result in higher efficacy in subsequent training applications via a process of generalization; alternatively, acquisition of multiple communication responses across reinforcer classes may result in relatively more errors (e.g., emission of previously taught responses that contact extinction) that may temporarily increase rates of challenging behavior.…”
Section: Methodsmentioning
confidence: 99%
“…For example, an individual with challenging behavior that is maintained by access to both attention and tangibles may continue to engage in challenging behavior (i.e., low treatment efficacy) if they are taught a communicative response for attention in the absence of tangible items. Another basis for selecting this variable was the potential influence of previously taught mands on treatment efficacy for newly taught mands (e.g., Banerjee et al, 2022;Lambert, Bloom, et al, 2017;Lambert et al, 2015Lambert et al, , 2020…”
Section: Single or Multiple Functionsmentioning
confidence: 99%
“…By having a repertoire of multiple appropriate mands, individuals may be more likely to obtain reinforcement, avoid contacting extinction, and thereby preclude resurgence Lambert et al, 2015). Neely et al (2020) and Banerjee et al (2022) demonstrated how topographically distinct mands (i.e., English, Spanish) can differentially impact the probability of reinforcement from a local verbal community proficient in only one of the two languages. When the receptive repertoire of therapists "shifted" from the language trained during FCT to the alternative language, resurgence of problem behavior occurred.…”
Section: Expanding the Operant Classmentioning
confidence: 99%
“…When the receptive repertoire of therapists “shifted” from the language trained during FCT to the alternative language, resurgence of problem behavior occurred. When the researchers adapted FCT to include mands in both languages (Neely et al, 2020) and provided training on alternative‐response variation (Banerjee et al, 2022), resurgence no longer occurred because the alternative response continued to produce reinforcement.…”
Section: Relapse‐mitigation Proceduresmentioning
confidence: 99%
“…Authors commonly described caregivers (Ghaemmaghami et al, 2021), peers (e.g., Austin et al, 2015), and a variety of confederates (adults, children, simulations; Stocco & Thompson, 2015) as implementers. In addition, the ecological validity of the language used by the implementer during an assessment of dual‐language communication training was discussed by Banerjee et al (2022). Finally, nine studies were coded unclear because the aspect of the study referenced by the term ecologic* was not clear enough to otherwise categorize.…”
Section: The Term “Ecological Validity” In Jabamentioning
confidence: 99%